2018
DOI: 10.1186/s13023-018-0784-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical and genetic spectrum of 70 patients with ACAD9 deficiency: is riboflavin supplementation effective?

Abstract: BackgroundMitochondrial acyl-CoA dehydrogenase family member 9 (ACAD9) is essential for the assembly of mitochondrial respiratory chain complex I. Disease causing biallelic variants in ACAD9 have been reported in individuals presenting with lactic acidosis and cardiomyopathy.ResultsWe describe the genetic, clinical and biochemical findings in a cohort of 70 patients, of whom 29 previously unpublished. We found 34 known and 18 previously unreported variants in ACAD9. No patients harbored biallelic loss of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 35 publications
1
63
0
1
Order By: Relevance
“…45 Therapeutic response to riboflavin supplementation was reported in 65% of treated patients in one large multinational cohort of ACAD9 deficiency. 48 Riboflavin responsiveness has also been reported in other forms of complex I deficiency. 49 It is possible that FMN may stabilize the complex I holoenzyme.…”
Section: Disorders Of the Human Flavoproteomementioning
confidence: 96%
“…45 Therapeutic response to riboflavin supplementation was reported in 65% of treated patients in one large multinational cohort of ACAD9 deficiency. 48 Riboflavin responsiveness has also been reported in other forms of complex I deficiency. 49 It is possible that FMN may stabilize the complex I holoenzyme.…”
Section: Disorders Of the Human Flavoproteomementioning
confidence: 96%
“…We report the first description of a successful pregnancy of a woman with mitochondrial cardiomyopathy and myopathy related to ACAD9 . Most of the historical cases with ACAD9 deficiency including our patient's brother died in early childhood 5 . Due to early riboflavin treatment our patient achieved adulthood and is now 29 years old.…”
Section: Discussionmentioning
confidence: 80%
“…Haack et al 10 tested in 2010 the impact of riboflavin supplementation on mutant cell cultures from two patients with ACAD9 mutations and found a significant increase in complex I activity. Repp et al 5 reported patients with predominant myopathic features who had alleviation of symptoms with riboflavin treatment. There was a significant increase in survival in the treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…show that riboflavin can be beneficial for patients with ACAD9 gene defects [66][67][68], high-fat diet for those with TMEM126B gene defects [69] and thiamine for those with SLC19A3 gene defects as reported in Chapter 4, [70][71][72]. Early start with these treatments prevents symptoms from occurring and can be lifesaving, for example, by preventing fatal Leigh Syndrome in patients with SLC19A3…”
Section: Treatment and Prevention Of Mitochondrial Diseasementioning
confidence: 97%